Strengthening Islamic Education Through Dakwah On The Street: A Phenomenological Study Of Marginalized Communities In Pare-Kediri - Thoriquttyas, Titis; Ahsin, Nurul; Musoffa, Yusron (LP2M IAIN kUDUS, 2026)
Limited access to formal and mosque-based Islamic education often leaves marginalized informal workers excluded from sustained religious learning. This study explores the meaning and practice of Dakwah on the Street in Pare–Kediri as a form of community-based nonformal Islamic education. Using a phenomenological approach, the study involved one principal dakwah practitioner and eighteen participants, including pedicab drivers, scavengers, parking attendants, day laborers, and other informal workers. Data were collected through in-depth interviews, participant observation, and documentation between mid-2025 and the end of 2025 and analyzed using Moustakas’ phenomenological procedures. Findings show that Dakwah on the Street functions not merely as a religious activity but as a transformative educational process fostering spiritual awareness, social solidarity, and personal empowerment. The phenomenological synthesis identifies five essential characteristics: social empathy as the basis of trust-building, dialogical spirituality through reflective learning, public space pedagogy that turns streets into educational domains, transformative consciousness that strengthens religious identity and agency, and practical resilience that sustains learning despite structural limitations. These findings indicate a shift from institution-centered dakwah toward a more humanistic, participatory, and emancipatory model of Islamic education. The study proposes a framework of Street-Based Transformative Islamic Pedagogy and offers practical insights for strengthening community-based dakwah among marginalized populations.